The uncertain future of a big promise - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Remember those slogans from the 1970s? 'Fish farming for all' and 'Fishing is good for you and fish is good for you' were the enthusiastic messages of family fish-farming campaigns. Small-scale fish rearing was easy, or so we thought then, and a...